Chlorella vulgaris and Porphyridium purpureum: two microalgae with polysaccharides and other potential valuable compounds - Ferreira, Andreia Filipa Sousa (2022)
Chlorella vulgaris and Porphyridium purpureum are two eukaryotic microalgae that have been highlighted from the biotechnological point of view due to their capability of producing multiple interesting metabolites, such as pigments and polysaccharides, beyond protein and lipids. Chlorella vulgaris is green due to the high cholorophyll content, representing a valuable source of this food aditive. However, since chlorophylls are sensitive compounds, they degrade easily by various mechanisms during storage. Aiming to find food grade suitable conditions for isolated chlorophylls preservation, C. vulgaris chlorophylls were extracted with 96% ethanol to study the influence of temperature, light, alkaline conditions, and modified atmosphere on the stability of the color in ethanolic solutions. Under the conditions used, the color loss was mainly due to the intense light (photoperiod 24 h), followed by the hight temperature (60 °C). The loss of green color in the ethanolic solution with temperature followed the first-order kinetic, being more significant between 28 and 60 °C, with an activation energy of 74 kJ/mol. To lower temperatures C. vulgaris chlorophylls showed resistance to the degradation when preserved in ethanol solutions. The addition of NaOH and the inert argon-rich atmosphere did not exhibit a statistically positive effect on the color preservation. Thus, C. vulgaris ethanolic extract showed to be more stable when protected from light at room temperature or bellow. C. vulgaris ethanolic extract showed to be a suitable natural food additive to coloring food stuffs. As case of study, the cooked cold rice was colored to be used in sushi. The color remained stable up to 3 days of storage at 4 ºC, either in the presence or absence of light. Beyond the high content in chlorophylls, C. vulgaris is rich in starch and structural polysaccharides that could have also great potential to be valued as food ingredients. Therefore, to fulfill this hypothesis, starch digestibility was evaluated in raw and boiled biomass, showing 43% and 71% of glucose released, respectively. The low extraction yield of starch obtained with water (13%) allowed to infer protein hindrance. This was overcome by 1 M and 4 M KOH aqueous solutions that allowed to obtain an additional 51% of starch. The final residue left showed that only 16% of total starch remained unextracted. KOH solutions allowed also to obtain galactans composed by 1,3-, 1,6- and 1,3,6-linked galactose residues. These linkages were also observed in the polysaccharides recovered from the growth medium, showing similarity between the exopolysaccharides and those present in the cell wall. The extracellular polymeric material revealed in vitro immunostimulatory effect on B lymphocytes. Porphyridium purpureum, also recognized as Porphyridium cruentum, is a red saline microalga that have been aroused commercial interest to be used for feeding fish in aquaculture. This microalga is rich in proteins and floridean starch, having the ability to excrete high levels of sulfated polysaccharides (sEPS) into the growth medium. P. purpureum is easily cultivated and could change their growth rate and composition in response to environmental variations. Thus, the impact of growth medium salinity (18, 32, and 50 g/L NaCl) on P. purpureum cells growth, biomass composition and on the extracellular polysaccharides production yield and chemical structure were evaluated. A maximum growth estimated as 5.7×106 cells/mL was obtained for 32 g/L of NaCl, after 19 days of growth. Besides biomass composition was not greatly changed, the sEPS excretion yield reflected the effect of salinity, higher for 32 g/L of NaCl (90 mg/L). The growth medium salinity slightly changed the sulfation pattern of the glucuronoglucogalactoxylan, since sEPS produced from P. purpureum grown at lower salinity tend to be more sulfated in O-3 position of xylose and O-6 position of glucose, while at higher salinity the sEPS tend to be more sulfated in O-4 position of xylose and glucose. The sEPS produced at higher salinity also revealed higher content of linear 2-Gal, 3-Gal, and 4-Gal residues. In all samples, the most representative sugar residues were constituted by t-Xyl, t-Xyl4S, 3-Xyl, 4-Xyl, t-Glc, 3-Glc6S, t-Gal, and 2,3,4-Gal. The sEPS showed immunostimulatory effect on B lymphocytes in vitro, similarly to the effect also demonstrated by the C. vulgaris extracellular polysaccharides. P. purpureum sEPS could be produced at large scale at an outdoor 800 L-flat panel photobioreactor with higher excretion yield (144 mg/L), revealing the potential of industrial production and commercialization of sEPS. In conclusion, this PhD thesis significantly upgraded the knowledge about the biotechnological potential of C. vulgaris pigments and both starch and exopolysaccharides, as food ingredients, with the additional commercial advantage of the possibility of these metabolites’ co-extraction. Moreover, P. purpureum sEPS revealed biotechnological potential to be used in aquaculture to enhance humoral immunoactivity of fish.